THE EFFECT OF PROBLEM BASED LEARNING MODEL AND LEARNING MOTIVATION ON THE STUDENTS' LEARNING OUTCOMES OF SMP NEGERI 1 BABALAN - Devi Ariastika; Hasruddin Hasruddin; Aman Simare-mare (Sensei International Journal of Education and Linguistic, 2022)
This research aims to:(1) Knowing the effect of the PBL learning model on the science learning outcomes of heat and its transfer materials; (2) Knowing the effect of learning motivation on science learning outcomes for the subject matter of Heat and Its Transfer; and (3) Knowing the effect of the interaction of the PBL learning model and learning motivation on the science learning outcomes of the subject matter of Heat and Its Transference. The sample in this study is student Class VII SMP Negeri 1 Babalan Academic year 2021/2022 as many as 54 students. Data collection through learning outcomes test and critical thinking ability test. Hypothesis testing is done by using the Two Way Anova test. The results showed that: (1) Model problem based learning provides a positive difference to the science learning outcomes of seventh grade students of SMP Negeri 1 Babalan in the 2021/2022 academic year (Fcount = 9.062 and sig. 0.004 <0.05); (2) Learning motivation gives a positive difference to the science learning outcomes of seventh grade students of SMP Negeri 1 Babalan in the 2021/2022 academic year (Fcount = 4.283 and sig. 0.044 <0.05); and (3) There is an interaction of problem based learning model and learning motivation on science learning outcomes for seventh grade students of SMP Negeri 1 Babalan in the 2021/2022 academic year (Fcount = 6249 and sig. 0.016 < 0.05).